Acute respiratory failure in influenza as a cause of out-of-hospital cardiac arrest - Šín, Robin; Sedláček, Dalibor; Kubiska, Miroslav (Klinicka mikrobiologie a infekcni lekarstvi, 2024)
Influenza is an infectious disease caused by influenza A, B, and sometimes C viruses. The disease is preventable in all age groups thanks to annual seasonal vaccination. Population groups at high risk of severe illness with complications include seniors, pregnant women, and young children. As our case report shows, an unvaccinated person of working age in good health can suffer life-threatening complications with untreated influenza. The most common complications include bacterial pneumonia, respiratory insufficiency, and cardiovascular problems. Up to 645,000 flu-related deaths are estimated each year.
Keywords: respirační insuficience; zástava srdce mimo nemocnici; Female; Out-of-Hospital Cardiac Arrest; Adult; dospělí; Respiratory Insufficiency; chřipka lidská; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Acute Disease; akutní nemoc; Influenza, Human